Decreasing the Overpotential of Aprotic Li‐CO2 Batteries with the In‐Plane Alloy Structure in Ultrathin 2D Ru‐Based Nanosheets. (4th May 2022) - Wang, Yunhao; Zhou, Jingwen; Lin, Chao; Chen, Bo; Guan, Zhiqiang; Ebrahim, Amani M.; Qian, Guannan; Ye, Chenliang; Chen, Lin; Ge, Yiyao; Yun, Qinbai; Wang, Xixi; et al.
Abstract: The aprotic Li‐CO2 battery is emerging as a promising energy storage technology with the capability of CO2 fixation and conversion. However, its practical applications are still impeded by the large overpotential. Herein, the general synthesis of a series of ultrathin 2D Ru‐M (M = Co, Ni, and Cu) nanosheets by a facile one‐pot solvothermal method is reported. As a proof‐of‐concept application, the representative RuCo nanosheets are used as the cathode catalysts for Li‐CO2 batteries, which demonstrate a low charge voltage of 3.74 V, a small overpotential of 0.94 V, and hence a high energy efficiency of 75%. Ex/in situ studies and density functional theory calculations reveal that the excellent catalytic performance of RuCo nanosheets originates from the enhanced adsorption toward Li and CO2 during discharge as well as the elevated electron interaction with Li2 CO3 during charge by the in‐plane RuCo alloy structure. This work indicates the feasibility of boosting the electrochemical performance of Li‐CO2 batteries by in‐plane metal alloy sites of ultrathin 2D alloy nanomaterials. Abstract : A one‐pot wet‐chemical method is developed to synthesize ultrathin 2D Ru‐M (M = Co, Ni, Cu) alloy nanosheets. As a proof‐of‐concept application, RuCo nanosheets are utilized as cathode catalysts for Li‐CO2 batteries, which demonstrate a low charge voltage and a small overpotential, surpassing most of the reported metal and metal‐based electrocatalysts.